EVOLUTION OF SOURCES IN ROMANIAN LEGAL SYSTEM - Horaţiu MĂRGOI (Challenges of the Knowledge Society)
The mechanisms by which social relationships are strengthened depend of the law maker's capacity to create an optimal juridical environment. Social function of juridical messages emitted by the Legislator it can be completed by the role of jurisprudence and case law. The reason of being of Laws is the citizens to be obedient to the prescriptions of rules. This must be the major interest of the Legislator and justifies efforts to make the Law easily perceived. Protection against legislation's inflation is for certain what citizens ask from Legislator, but most of of, the justice seeker is demanding a predictability of justice. The danger brought by the judge activity interference in legislative is no longer sufficient to offset the risk of perpetuating a non-unitary judicial practice. The damage even of the smallest incoherent legal practices is felt among both judges and litigants and must be prevented.